2015
DOI: 10.1093/hmg/ddv016
|View full text |Cite
|
Sign up to set email alerts
|

Early white matter abnormalities, progressive brain pathology and motor deficits in a novel knock-in mouse model of Huntington's disease

Abstract: White matter abnormalities have been reported in premanifest Huntington's disease (HD) subjects before overt striatal neuronal loss, but whether the white matter changes represent a necessary step towards further pathology and the underlying mechanism of these changes remains unknown. Here, we characterized a novel knock-in mouse model that expresses mouse HD gene homolog (Hdh) with extended CAG repeat- HdhQ250, which was derived from the selective breeding of HdhQ150 mice. HdhQ250 mice manifest an accelerated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(112 citation statements)
references
References 90 publications
5
107
0
Order By: Relevance
“…Numerous studies have also reported extensive alterations in white matter tract (WMT) architecture in HD cases and animal models (Bohanna et al, 2011; Jin et al, 2015; Paulsen et al, 2006; Phillips et al, 2014). Thus, we next examined the status of myelination of cortical deep layers at 12-months of age.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have also reported extensive alterations in white matter tract (WMT) architecture in HD cases and animal models (Bohanna et al, 2011; Jin et al, 2015; Paulsen et al, 2006; Phillips et al, 2014). Thus, we next examined the status of myelination of cortical deep layers at 12-months of age.…”
Section: Resultsmentioning
confidence: 99%
“…Impaired myelination has been reported in HD patients (Bartzokis et al, 2007) and mouse models (Xiang et al, 2011; Jin et al, 2015). The molecular mechanisms underlying this white matter abnormality are largely unknown, although PGC-1α deficiency (Xiang et al, 2011) and altered proliferation of oligodendrocyte precursor cell (Jin et al, 2015) could be contributing factors.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms underlying this white matter abnormality are largely unknown, although PGC-1α deficiency (Xiang et al, 2011) and altered proliferation of oligodendrocyte precursor cell (Jin et al, 2015) could be contributing factors. Interestingly, our study revealed that p75 NTR - and sortilin-immunoreactivities are both significantly elevated in a subset of immature striatal oligodendrocytes in aged zQ175 HD mice, and this correlates with myelination defect in the HD striatum.…”
Section: Discussionmentioning
confidence: 99%
“…HdhQ150 mice displayed some HD symptoms that seem more severe in homozygous mice [33,39,40]. Recently, heterozygous hdhQ250 mice have been generated from hdhQ150 by selective breeding and shown more severe neurological symptoms than heterozygous hdhQ150 mice [41]. Hdh4/Q80 and Hdh6/Q72 mice have also been obtained by replacement of short CAG repeat with 72 or 80 CAG repeat expansions in htt murine gene context.…”
Section: Mouse Models Of Cag Repeat Instabilitymentioning
confidence: 99%